2021
DOI: 10.1097/iae.0000000000002921
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Cystotomy With or Without the Fibrinogen Clot Removal for Refractory Cystoid Macular Edema Secondary to Diabetic Retinopathy

Abstract: Purpose: To show the long-term effect of cystotomy with or without fibrinogen clot removal for refractory cystoid macular edema secondary to diabetic retinopathy.Methods: Retrospective analyses of the medical records of 30 eyes of 30 patients with refractory cystoid macular edema secondary to diabetic retinopathy who had followed up for 12 months after the surgery were performed.Results: There were 15 men and 15 women. The mean ± SD age was 68.4 ± 7.9 years. The best-corrected visual acuity (logarithm of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Recently, Imai et al reported the effectiveness of cystotomy for long-term anatomical and functional improvements of refractory cystoid macular edema secondary to DR. However, it is necessary to accumulate many cases for the concrete conclusion of the effectiveness of cystotomy [155,156]. Overall, there is the possibility of the same risks as other vitrectomies, and care must be taken when choosing potential patients.…”
Section: Treatment For Dmementioning
confidence: 99%
“…Recently, Imai et al reported the effectiveness of cystotomy for long-term anatomical and functional improvements of refractory cystoid macular edema secondary to DR. However, it is necessary to accumulate many cases for the concrete conclusion of the effectiveness of cystotomy [155,156]. Overall, there is the possibility of the same risks as other vitrectomies, and care must be taken when choosing potential patients.…”
Section: Treatment For Dmementioning
confidence: 99%
“…The removed translucent mass was thought to be a fibrinogen clot based on the characteristic clinical findings, such as translucent color, irregular shape, and size (see Video, Supplemental Digital Content 1, http://links.lww.com/ICB/A122, which demonstrates the surgical process of cystotomy and en bloc removal of the fibrinogen-rich component of the cystoid lesion in this case). 6,7 The CME rapidly disappeared after surgery. Three years after the operation, the patient had best-corrected decimal visual acuity of 0.5 (Snellen equivalent, 20/40) at the last medical examination, and the CME has not recurred (Figure 2, A-F).…”
Section: Case Reportmentioning
confidence: 99%
“…Surgical procedures for refractory CME that include cystotomy and en bloc removal of the fibrinogen-rich component of the cystoid lesion have been reported to improve visual acuity and the macular edema secondary to several retinal vascular disorders, such as diabetic retinopathy and retinal vein occlusion. 6,7…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that 7 of 22 eyes had improved vision, 13 had no change, and 2 had worsened after surgery. We recently reported that the accumulation of fibrinogen in cystoid cavities of rfCME secondary to branch retinal vein occlusion (BRVO), DR, and idiopathic macular telangiectasia type 1, and the removal of fibrinogen clots with cystotomy showed postoperative functional and anatomical improvements 7 , 8 . These outcomes suggest the effectiveness of cystotomy and fibrinogen clot removal for rfCME secondary to BRVO, but the details have not been investigated.…”
Section: Introductionmentioning
confidence: 99%